Shape optimization of arch dams under dynamic load - Ülker, Mehmet; Savaş, Sedat (My University, 2006)
This paper presents shape optimization of a concrete arch dam using a noval approach. For this purpose, the symmetrical valley shape, which corresponds to an arch dam of type 5 from The Arch Dams Committe report of the Institution of Civil Engineers is selected. The geometry of the arch dam is described by two polynomial functions. In this study, the objective function is volume concrete and the constraints are stress limits of concrete and design variables. The external loads are pressure by the water behind the dam and the self-weight of the structure for static analysis. Then additional load for dynamic analysis are done, taking the S-69-E component of TAFT earthquake and then East-West component of Erzincan earthquake into account. The iterative optimization process is initiated by modeling the three dimensional design spaces by eight node solid elements with three degrees of freedom at each node. The finite element analysis of is the system first carried out under external loading for static analysis and then for dynamic analysis, At the end of solution, maximum, minimum principal stresses and coefficients of polynomial are compared to the design variables. This progress is continued until the optimum solution is reached. The conclusion of progress is compared to old analyses and better results solution is obtained which is given graphically.
Dinamik yük altinda kemer barajlarin şekil optimizasyonu
Keywords: Dynamic analysis; Finite element; Shape optimization; The concrete arch dam